Sudan : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2021)
This Joint Staff Advisory Note (JSAN) reviews the Sudan Poverty Reduction Strategy Paper (PRSP) for the period 2021-2023. The PRSP was prepared by the Government of Sudan, drawing on lessons learned from the implementation of the 2012 interim poverty reduction strategy paper (I-PRSP).1 The PRSP was approved by the Council of Ministers on May 11, 2021. The government submitted the PRSP to IDA and the IMF on May 12, 2021 to fulfill the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative's poverty reduction strategy requirement.